Decoupling Control Strategy of IPT System Based on Optimal Efficiency Load Tracking - Wenmei Hao; Liwei Zhang; Sanmu Xiu; Fengyu Leng (Journal of Advanced Transportation)
The inductive power transmission system is applied to urban rail transit. Due to the limitations of the volume and coupling coefficient of the inductive coupling mechanism and the fact that the fluctuation of air gap in its movement will cause the fluctuation of mutual inductance value, DCDC booster link should be added to the side, rectifying side, to improve the output voltage level and stability. At present, most of the existing control strategies are based on the original side information communication. However, in the application of dynamic wireless charging in urban rail transit, the primary and secondary side coils are in the process of relative movement, so it is relatively difficult to establish reliable real-time communication, and it is easy to be interfered by electromagnetic transmission process, resulting in large errors. This paper analyzes the relationship between load and efficiency of IPT system applied to urban rail transit in detail and obtains the optimal load matching strategy of optimal efficiency. At the same time, an independent control strategy is proposed to eliminate the information communication of the primary and secondary sides and realize decoupling control. Finally, a simulation model is built to verify the effectiveness of the control strategy.